Munasabah Al-Ayat Wa As-Suwar - Lasepe, Risky Rinaldi; Ondeng, Syarifuddin; Shahib, Muhammad Amin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
In this paper, the importance of understanding the munasabah al-ayat and al-suwar in the Qur'an has been discussed. Munasabah plays a crucial role in helping readers understand the meaning and context of revelation. By analyzing the relationship between verses and letters, we can dig deeper into the messages contained in the Qur'an. The study of munasabah al-ayat and al-suwar is essential to enrich our understanding of the Qur'an. By understanding this relationship, we can provide a more accurate and comprehensive interpretation of the text of the Qur'an. This can also strengthen religious practices and understanding of Islamic teachings as a whole. It is hoped that further research can be conducted to dig deeper into munasabah al-ayat and al-suwar, and their implications in everyday life. This research can include comparative studies between different interpretations and different analytical approaches, so that it can provide broader insights into the understanding of the Qur'an.